Objectives As Guarantee Of Liability In Problem Credit Agreements (Study At PT. Bank Sumut Utama Branch) - Vinno Isvara (Journal of Law Science, 2021)
A credit agreement is an agreement between a bank as a creditor and a customer as a debtor to lend a certain amount of funds to the debtor. However, it often happens that when the credit has been given to the debtor, it turns out that the debtor cannot return the amount of money, goods or services that were promised to be returned at a predetermined time and becomes a non-performing loan so that the bank cannot withdraw the funds that have been given. Here the bank makes a rule, if someone wants to borrow credit then there must be a guarantee in the form of Mortgage which is regulated in the Mortgage Law Number 4 of 1996. Dependents can be auctioned and executed.The problem that will be discussed in writing this thesis is how is the position of the object as collateral for Mortgage in granting credit at PT. Bank Sumut Main Branch, how is the management of non-performing loans with mortgage guarantees at PT. Bank Sumut Main Branch and whether the collateral can be executed directly in an effort to resolve non-performing loans at PT. Bank Sumut Main Branch. In writing this thesis, the method used is library research, namely: research is carried out by obtaining material from the library in the form of books, scholarly works of scholars, laws and regulations, magazines, and others that have related to the title of this thesis. The research was also carried out by means of field research (Field Research), namely: data collection, consultation with Mr. Muhsin Adlin, SH as Head of Credit Administration at PT. Bank Sumut Caban Utama, where this consultation aims to find out various matters relating to Materials as Guarantees for Mortgage in Problematic Credit Agreements at PT. Bank Sumut Main Branch.